ANALYZING THE CONTENT PREFERENCES AND CHOICES OF THE INDIAN OTT CONTENT CONSUMER (SERIES & DIRECT TO OTT FILMS) - Khader, Zareena (Digital Repository of Theses, 2023)
The accessibility and mobility of content created an upsurge in the demand for content amongst various consumer segments. The era of digital communication has transformed the way the story tellers told their stories to the audiences. The content created for digital media stood out from the traditional ways of storytelling and content production. Taking a leap from the digital world of Meta and YouTube, is the world of streaming platforms that swooned the other media platforms by the sheer choice of the content and its penetration into the loyal consumer base that the traditional media took eons to build on. The audience had a refreshing break from the sitcoms and melodramatic soap operas to refreshing stories that did not make their way to the box office. A world full of stories, narratives from the hinterland to Queen’s palace or even the kingdoms of the seven provinces and their game of thrones, the tales across genres, gripping performances, and no barriers of censor of subjects that can stir social or political discussions or discords – that is the world of OTT that we now live in.